Quantitative study on experimentally observed poroelastic behavior of Berea sandstone in two‐phase fluid system. Issue 8 (6th August 2014) - Goto, Hiroki; Aichi, Masaatsu; Tokunaga, Tomochika; Yamamoto, Hajime; Ogawa, Toyokazu; Aoki, Tomoyuki
Abstract: Coupled two‐phase fluid flow and poroelastic deformation of Berea sandstone is studied through laboratory experiment and numerical simulation. In the experiment, compressed air was infiltrated from the bottom of a water‐saturated cylindrical Berea sandstone sample under hydrostatic external stress condition. Both axial and circumferential strains at half the height of the sample showed sudden extension and monotonic and gradual extension afterward. Numerical simulation based on thermodynamically consistent constitutive equations was conducted in order to quantitatively analyze the experimental results. In a simulation assuming isotropy of material properties, the volumetric discharge rate of water at the outlet and one of the axial, circumferential, and volumetric strains at half the height of the sample were reproduced well by each parameter set, while the other two strains were not. When introducing transverse isotropy, all the experimental data were reproduced well. In addition, the effect of saturation dependency of Bishop's effective stress coefficient on the deformation behavior of porous media was discussed, and it was found that strains, both axial and circumferential, are sensitive to the coefficient. Key Points: Poroelastic behavior of Berea sandstone for two‐phase fluid flow is observed The theory of multiphase thermoporoelasticity explains the experimental data The data are explained better by introducing anisotropy of material properties